Structural study of letrozole and metronidazole and formation of self-assembly with graphene and fullerene with the enhancement of physical, chemical and biological activities. Issue 15 (2nd September 2021) - Almuqrin, Aljawhara H.; Al-Otaibi, Jamelah S.; Mary, Y. Sheena; Mary, Y. Shyma; Thomas, Renjith
Abstract: Letrozole and metronidazole are two commonly used drugs for the management of breast cancer and parasitic infections, respectively. This manuscript attempts to study their structure, geometry, search for stable conformers using relaxed potential energy scan, spectral properties, quantum mechanical properties like energy and reactivity descriptors, intra molecular electron transfer properties, non-linear properties etc using various computational tools. It is found that these compounds will form a self-assembly with graphene sheets and fullerenes and exhibit a surface-enhanced Raman spectra and enhancement in non-linear optical properties when compared to the single molecule. The electronic absorption behavior of the compounds was studied using TD-DFT method. Global chemical reactivity descriptors and activity sites toward electrophilic and nucleophilic attack have been discussed. Studies of intra molecular electron transfer gave information about the relative stability of the compounds. Molecular docking studies indicate that the pure compounds and their self-assemblies with graphene have excellent biological activities. Communicated by Ramaswamy H. Sarma